Alat Bantu Prediksi Kecepatan pada Gerak Lurus Berubah Beraturan Menggunakan Metode Interpolasi Berdimensi Satu - Nurullaeli Nurullaeli (UNIVERSITAS INDRAPRASTA PGRI, 2020)
The purpose of this study is to create a speed prediction tool in a uniformly accelerated linear motion using a single-dimensional interpolation method consisting of linear, cubic, cubic spline, and nearest neighbor interpolation methods. This tool is packaged in the form of Graphic User Interface (GUI) using Matlab programming language. This tool can be used as a medium of the analysis of the object speed experiencing a uniformly accelerated linear motion and a combination of several uniformly accelerated linear motions. Speed prediction results using linear, cubic, and cubic spline interpolation methods do not differ much from the results of analytical calculations, while speed prediction results using nearest neighbor interpolation method are less in line with the results of analytical calculations because nearest neighbor interpolation method will generate constant values around the data point. This tool can also be used as a learning medium to make it easier for students to learn the concept of uniformly accelerated linear motion in order to reduce the misconceptions in the material.